2-Carbamimidoylbenzoic Acid as a New Effective and Available Precursor for the Synthesis of Substituted 2-(Pyrimidin-2-yl)benzoic Acids - Tkachuk, Volodymyr A.; Shishkanu, Vyacheslav O.; Tkachuk, Tetiana M.; Shishkina, Svitlana V.; Hordiyenko, Olga V. (Synthesis, 2020)
A new approach to the synthesis of 2-(pyrimidin-2-yl)benzoic acids based on the ring contraction of the 2-carbamimidoylbenzoic acid [(2-amidinobenzoic) acid] with 1,3-dicarbonyl compounds and their synthetic equivalents has been developed. The intramolecular condensation of the obtained acids with 1,3-dielectrophiles proceeds with the formation of the 4,6-dihydropyrimido[2,1-a]isoindole-4,6-dione system, the pyrrolidone ring of which is easily opened under the action of weak nucleophiles. The reaction of 2-amidinobenzoic acid with chromones, which have an aryloxy group at 3-position does not stop at the step of pyrimidine ring formation and undergoes further spontaneous cyclization into 2-(benzo[4,5]furo[3,2-d]pyrimidin-2-yl)benzoic acids.
Keywords: 2-carbamimidoylbenzoic acid; ring closure; 2-(pyrimidin-2-yl)benzoic acids; 4,6-dihydropyrimido[2,1-a]isoindole-4,6-dione; chromone ring opening; green chemistry